Active Listening: Its Impact on Language Learning and Understanding of Education Students - Ambubuyog, Ella Mae I.; Laumoc, Glenda Lyn C.; Mantac, Francine Hazel A.; Pagulayan, Freda Mae C.; Sayson, Cris Jan Era C.; Velasco, Aliena Claire M.; Biray, Ersyl T. (Future Science / FSH-PH Publications, 2023)
In learning a new language, there are four macro skills that a learner must develop and use: listening, reading, speaking, and writing. In academic environments such as schools, these macro skills are taught and improved every day to suit the needs of learners. Language learners are often trained when or how they should talk; however, learners are seldom taught how they should listen. This descriptive quantitative study revolved around the utility of listening, how it affects upon the acquired macro skill, specifically, active listening to education students specializing in English from a state institution in Panay Island, Western Visayas, Philippines, as well as its impact on their language learning and understanding. Findings revealed that active listening is vital in the language learning and acquisition with its effects found on multiple aspects of the learning process. It had an underlying impact on phonology, morphology, and pragmatics. It is implied that active listening as an underrated skill should be attended to by language teachers who take charge in teaching macro skills in communication.